2017
DOI: 10.1186/s12199-017-0646-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of air pollutants on pulmonary function among students: a panel study in an isolated island

Abstract: BackgroundMany epidemiological studies on the health effects of air pollutants have been carried out in regions with major sources such as factories and automobiles. However, the health effects of air pollutants in regions without major sources remain unclear. This study investigated the acute effects of ambient air pollution on pulmonary function among healthy students in an isolated island without major artificial sources of air pollutants.MethodsA panel study was conducted of 43 healthy subjects who attende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…Epidemiological studies from East Asia have detected an association between AD and adverse health events, including respiratory and cardiovascular diseases [6][7][8]. Children appear to be more vulnerable than adults, both in terms of susceptibility and response to environmental changes, including air pollution [9][10][11][12][13]. In particular, children with bronchial asthma are more easily affected by environmental changes [14].…”
mentioning
confidence: 99%
“…Epidemiological studies from East Asia have detected an association between AD and adverse health events, including respiratory and cardiovascular diseases [6][7][8]. Children appear to be more vulnerable than adults, both in terms of susceptibility and response to environmental changes, including air pollution [9][10][11][12][13]. In particular, children with bronchial asthma are more easily affected by environmental changes [14].…”
mentioning
confidence: 99%
“…Even in the suburbs, the use of coal has led to a high prevalence of persistent cough in children. We were reported that on an isolated island without major artificial sources of air pollutants, changes in the concentrations of air pollutants acutely influenced the pulmonary function of healthy subjects [38]. On the other hand, the increased prevalence of respiratory symptoms may also affect the burning of solid waste at the open dumpsites in the gers districts.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are critical for inner-city schools because of their close proximity to highways, heavy traffic, and industrial buildings. These establishments tend to be located centrally, among condensed traffic, with sites of idling cars increasing air pollution within and around the school 84,83,85 NO 2 , is generated from fossil fuel combustion in homes and outdoors but can be found in other settings. Gaffin et al, showed a non-significant temporally distinct association of NO 2 levels measured in inner-city school classrooms with airflow obstruction in children with asthma.…”
Section: Physical Environment Air Pollutionmentioning
confidence: 99%